A Review of Atlanta's "FUBU": On Power. Issue 3 (2nd October 2018) - Quiros, Julian
Abstract: This media review focuses on one of Atlanta 's episodes entitled "FUBU." The episode is utilized as a proxy to provide a critique of American society and its power relations in everyday life. Atlanta and its writers use television as their vehicle to create critical and constructive discourse in spaces that they would otherwise not be able to physically occupy. Out of this, the hope is that this discourse leads to healthier interaction in the educational spaces facilitated by educators with an understanding of the social forces at play.